The crime of drug trafficking in the Spanish legal system. A review of some of the most important issues of current criminal regulation - Casanueva Sanz, Itziar (2021)
This article makes a brief presentation on the Spanish criminal regulation in relation to the crime of drug trafficking and the precepts applicable to those people who commit crimes as a result of their drug dependence. Although the existing link between drugs and crime there is no unanimity on what is the mechanism that the State should use to deal with such consumption and trafficking, the Spanish legislator has opted for a broad regulation of the crime of drug trafficking, which results certainly excessive. That is why the regulation of this crime will be analyzed in article 368 of the Spanish Criminal Code.